Mental Toughness in Competitive Tennis: Relationships with Resilience and Stress - Cowden, Richard G.; Meyer-Weitz, Anna; Oppong Asante, Kwaku (Frontiers in Psychology, 2016)
The present study investigated the relationships between mental toughness (MT), resilience, and stress among competitive South African tennis players. A total of 351 tennis players participating at various competitive standards completed the Sport Mental Toughness Questionnaire, the Resilience Scale for Adults, and a modified version of the Recovery-Stress Questionnaire for Athletes. The results indicated that total MT was positively associated with total resilience (r = .59), but negatively associated with total stress (r = -.44). The resilience subscales of perception of self, perception of future, social competence, and social resources, but not family cohesion, significantly predicted total MT (R2 = .35). Both total resilience and total MT significantly predicted total stress (R2 = .21). Based on the findings, interrelations between MT and resilience are explored, implications outlined, and additional research is suggested to ascertain the contextual relevance and outcomes associated with each construct in sport.